Discourse on Reporting the Palestine-Israel Conflict “Inclusion Strategy in the News of the Shooting of Shireen Abu Akleh (Al Jazeera Journalist) on BBC Arabic Newspaper” - Nawawi, Hasby Achmad; Kulsum, Umi (Litteratura: Jurnal Bahasa dan Sastra, 2023)
This study aims to analyze the inclusion strategy in constructing the news about the shooting of Al Jazeera journalist Shireen Abu Akleh. The method used is descriptive analysis with the object of research, namely news texts                          "شيرين أبو عاقلة: إدانات واسعة ودعوات لإجراء تحقيق في مقتل مراسلة الجزيرة أثناء تغطيتها لغارة إسرائيلية regarding the shooting of Shireen Abu Akleh (Palestinian-American Journalist) on BBC Arabic on May 11, 2022. The data was collected through document review method using the close reading techniques. In analyzing the data, this research applies the theory of inclusion in critical discourse analysis developed by Theo van Leeuwen. The results of the analysis show that BBC Arabic attempted to provide comprehensive and balanced coverage of Shireen Abu Akleh by focusing on the victim. However, this study also highlights the possible interests in the presentation of the news presented in the construction of the news. By identifying such patterns through inclusion strategies, this research provides a reminder to readers of the importance of critically observing news, considering context, and understanding potential biases that may be included in the presentation of news by international media such as BBC Arabic.